2011
DOI: 10.5114/jcb.2011.21036
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Investigations Adjuvant high dose rate brachytherapy for soft tissue sarcomas: initial experience report

Abstract: PurposeAdjuvant high-dose-rate brachytherapy (HDRBT) offers advantages over low dose rate brachytherapy (LDRBT), although there are little data on local tumor control and treatment related toxicity. We report outcome in patients with primary, recurrent, and metastatic extremity and superficial trunk soft tissue sarcoma.Material and methodsEleven patients (12 sites) with intermediate or high grade sarcoma were treated with adjuvant HDRBT following surgical resection. Patients were treated at 3.4 Gy fractions de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The results of this study and further studies have indicated that brachytherapy has no impact on local control for low grade soft tissue sarcomas. If brachytherapy is used, the dose is 40-45 Gy to a volume that includes all margins; when it's used as a boost in combination with externalbeam irradiation, a dose of 20-25 Gy is utilized [30]. In a study conducted at Memorial Sloan-Kettering Cancer Center (MSKCC), over a 15-year period, 202 patients with high-grade sarcoma of the extremities were treated with complete gross resection followed by brachytherapy delivered over 5 days, with a median dose of 45 Gy.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study and further studies have indicated that brachytherapy has no impact on local control for low grade soft tissue sarcomas. If brachytherapy is used, the dose is 40-45 Gy to a volume that includes all margins; when it's used as a boost in combination with externalbeam irradiation, a dose of 20-25 Gy is utilized [30]. In a study conducted at Memorial Sloan-Kettering Cancer Center (MSKCC), over a 15-year period, 202 patients with high-grade sarcoma of the extremities were treated with complete gross resection followed by brachytherapy delivered over 5 days, with a median dose of 45 Gy.…”
Section: Discussionmentioning
confidence: 99%
“…The place of brachytherapy as monotherapy is only valuable in low-risk situations or in case re-irradiation can be considered afterwards (15). If applied as a booster to adjuvant RT, brachytherapy is described to give excellent local control and limited toxic complications (18). However toxic side effects have been described (13,15).…”
Section: Discussionmentioning
confidence: 99%
“…A study was performed in eight patients with unresectable pancreatic head tumors, suffering from pain of high intensity who were candidates for palliative surgery due to jaundice and/or recurrent ileus ( 56 ). They underwent perioperative high dose rate brachytherapy with 192 Iridium implants.…”
Section: Applications In Pancreatic Cancer Therapymentioning
confidence: 99%
“…The patients who underwent perioperative palliative brachytherapy described more pain relief. Mean survival time was 6.7 months in the brachytherapy group, vs. 4.4 months in the group where no brachytherapy was performed ( 56 ).…”
Section: Applications In Pancreatic Cancer Therapymentioning
confidence: 99%